10.1371/journal.pmed.0020297 (CrossRef Listing of Deleted DOIs, 2000)
Poor mental health, including anxiety and depression, is prevalent among college students. Identifying protective factors is essential for enhancing mental health. Previous research suggests engagement in various communities may be important for mental health. This study examined the associations between engagement in community domains (e.g., family, school, work, and church) on individual mental health outcomes among college students. Participants (N = 379) were recruited through a general education undergraduate introductory psychology course. Participants completed a survey measuring anxiety, depression, flourishing, and community engagement. Data were analyzed using structural equation modeling (SEM) in MPlus8. The SEM demonstrated good fit to the data (RMSEA = .049, CFI = .966). Engagement across family, peer, church, and school domains was positively associated with higher individual flourishing, with peer engagement showing the strongest association (β = 0.26, p < .05). Higher flourishing was associated with lower levels of depression and anxiety. Indirect associations between community engagement and mental health outcomes through flourishing were significant across all domains (β = -.09, p < .05). School engagement was also independently associate with anxiety symptoms. These findings highlight the importance of fostering engagement across family, school, peer, and church domains, which may enhance individual flourishing and reduce depression and anxiety among young adult college students.